2017
DOI: 10.1139/cjb-2016-0314
|View full text |Cite
|
Sign up to set email alerts
|

Variations in nitrogen, phosphorus, and δ15N in Sphagnum mosses along a climatic and atmospheric deposition gradient in eastern Canada

Abstract: We examined concentrations of nitrogen (N) and phosphorus (P) and δ 15 N value in Sphagnum sections Acutifolia and Cuspidata inhabiting hummocks and hollows from 8 bogs along a transect from ~45 to ~55 °N in Ontario/Quebec. The N concentration in Sphagnum declined from South to North, correlating with a decrease in atmospheric N deposition. Although the overall N concentration was larger in hollows than hummocks, the pattern was inconsistent across the sites.There was a proportionally larger decline in P conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We assumed no inter‐provincial trade in fertilizers since this information is not available. Atmospheric deposition, typically neglected or regarded as a constant in previous studies (Chen & Graedel, 2016; Wironen et al., 2018), was assumed to be 0.4 kg P ha −1 y −1 , which is consistent with field observations (Živković et al., 2017). Irrigation water P was estimated by multiplying monitored P concentration of source water (0.05 mg L −1 ) (Little et al., 2010) by irrigation volume reported in Statistics Canada.…”
Section: Methodsmentioning
confidence: 64%
“…We assumed no inter‐provincial trade in fertilizers since this information is not available. Atmospheric deposition, typically neglected or regarded as a constant in previous studies (Chen & Graedel, 2016; Wironen et al., 2018), was assumed to be 0.4 kg P ha −1 y −1 , which is consistent with field observations (Živković et al., 2017). Irrigation water P was estimated by multiplying monitored P concentration of source water (0.05 mg L −1 ) (Little et al., 2010) by irrigation volume reported in Statistics Canada.…”
Section: Methodsmentioning
confidence: 64%
“…Many recent studies have reported increases in the N:P ratio in the soil, water, and plants of terrestrial and aquatic ecosystems (Blanes, Viñegla, Merino, & Carreira, ; Crowley et al, ; Hessen, ; Huang, Liu, et al, ; Jirousek, Hajek, & Bragazza, ; Lepori & Keck, ; Xu, Pu, Li, & Zhu, ; Yu et al, ; Zivkovic, Disney, & Moore, ) in response to “high levels of atmospheric N deposition” (Table ).…”
Section: Shifts In N:p Ratios Mediated By Anthropogenic Drivers Of Glmentioning
confidence: 99%
“…Biogeochemical evidence points to an important role for Sphagnum -associated prokaryotic populations in mediating critical ecosystem processes such as methane oxidation (methanotrophy) and nitrogen fixation (diazotrophy) ( 34 36 , 48 , 51 54 ). For example, Sphagnum -associated methanotrophs act as a natural methane biofilter and provide up to one-third of Sphagnum carbon needs ( 29 , 31 , 32 , 34 ).…”
Section: Introductionmentioning
confidence: 99%